Finding Gender in the Arctic: A Call to Intersectionality and Diverse Methods - Hoogensen Gjørv, Gunhild (Springer, 2017)
Source at https://doi.org/10.1007/978-3-319-57532-2_30 . The following chapter examines multiple aspects of including gender perspectives in Arctic research. In the chapter I discuss the definition and understanding of the concept of gender, and then move to the concept of “intersectionality” which recognizes the important linkages between multiple identities of gender, race, ethnicity, class, age, and other social categories. I then discuss both the ways in which gender has been addressed, though still minimally, in Arctic research, as well as some of the ways in which Arctic research is itself gendered. I then discuss how gendered perspectives add important insights into understanding security, and more specifically human security, in the Arctic.